Research of trust evaluation model based on dynamic Bayesian network - Hong-quan LIANG; Wei WU (Tongxin xuebao)
Trust evaluation model needs to be developed for trusted network.Based on interpersonal trust model in sociology,the trusted relationship between network nodes was researched,and a trust evaluation model based on dynamic bayesian network associating with time factor as proposed.The impact of authentication and network interaction behavior was fully considered,and historical interaction window,timelin factor and penalty factor were introduced.Also,the polymerization method of the direct trust de ee and indirect trust degree was given,and the dynamic adaptive ability of the model was improved as well as the calculation of the sensitivity and accuracy.Furthermore,the threaten of abnormal entity was effectively suppressed.Experimental results show that this model computes the trust degree more sensitively and effecti ly as well as better dynamic adaptivity compared with the traditional bayesian network model.